Infecting Cancer to Cure It: The Power of Oncolytic Viruses in Gynecologic Oncology – A Narrative Review - Kumar, Naina (Drug Research, 2025)
Gynecological cancers, including ovarian, cervical, and endometrial malignancies, contribute significantly to the global cancer burden. Oncolytic virotherapy (OVT), using both double-stranded DNA viruses (such as adenovirus, vaccinia, and herpesvirus) and single-stranded RNA viruses (including positive-sense viruses like coxsackievirus and poliovirus, and negative-sense viruses like measles and Newcastle disease virus), has emerged as a promising therapeutic approach. This review aims to evaluate the current state and future prospects of OVT in treating gynecological cancers.A literature search was conducted from December 2005 to December 2024 using databases like PubMed, Scopus, and Web of Science with keywords such as “oncolytic virotherapy,” “gynecological cancers,” and specific virus types. Studies were included after assessing the efficacy, safety, mechanisms of action, and combinatorial use of OVT with other therapies. Exclusions included non-English publications, non-gynecological cancer studies, and those without relevant clinical or experimental data. This review thoroughly explores OVT’s potential in gynecological cancer treatment.Oncolytic virotherapy demonstrates transformative potential for managing gynecological cancers. Whether used as monotherapy or in combination with other treatments, OVT shows promise in improving therapeutic outcomes and patient survival. However, further research is necessary to optimize its clinical application.
Keywords: adenovirus; cervical cancer; endometrial cancer; oncolytic virotherapy; ovarian cancer; virus